Non-performing loans, cost of capital, and lending supply: Lessons from the Eurozone banking crisis - Gabriella Chiesa; José Manuel Mansilla-Fernández (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2018)
This paper develops a theoretical model as a foundation of empirical analysis of the transmission channel of non-performing loans (NPLs) on bank cost of capital, credit and liquidity creation in the Eurozone. Empirical results confirm the model's predictions and suggest that holding non-performing loans increases the cost of capital for banks in the short-term and the long-term. Moreover, the increased cost of capital reduces credit and liquidity creation, and the more so the less capitalized is the bank. This phenomenon is found to be economically more significant for European periphery country banks than for core country banks. The identification of the transmission channel is robust to the Granger predictability test.
Keywords: G11; G21; G32; H63; 330; Cost of capital; credit supply; liquidity creation; NPLs; sovereign debt crisis